An Improved Secure Router Discovery Mechanism To Prevent Fake Ra Attack In Link Local Ipv6 Network - C. Arjuman, Navaneethan (2021)
In the Internet Protocol Version 6 (IPv6) network, Neighbour Discovery Protocol (NDP) plays a vital role in configuring the IPv6 address for any type of host. The IPv6 host will obtains the IPv6 address using Stateless Address Autoconfiguration (SLAAC). SLAAC was implemented using two types of key ICMPv6 NDP message protocol i.e Neighbour Discovery (ND) and Router Discovery (RD) in the IPv6 network. The RD messages consist of Router Solicitation (RS) and Router Advertisement (RA) messages. The standard RD by design do not have trust mechanism to authenticate the legitimate host and router. This design flaw within RD protocol has led to Fake RA attacks. Studies shows that the standard RD protocol is vulnerable to Fake RA attack where the host will be denied legitimate gateway. In order to address this issue, several prevention techniques have been proposed in the past to secure RD process.